2021 Update on Systemic Therapy for Breast Cancer - Anton Oseledchyk; Christian Kurzeder; Angela Kohler; Marcus Vetter (healthbook TIMES. Oncology Hematology)
Over the past years, new systemic therapies for advanced and metastatic breast cancer have emerged, resulting in significantly improved survival outcomes in this patient population. This article provides a summary of selected clinically relevant studies presented at the 2021 European Society for Medical Oncology (ESMO) Congress, American Society of Clinical Oncology (ASCO) Annual Meeting and San Antonio Breast Cancer Symposium (SABCS), including updated results from pivotal trials and new data on emerging therapies.